2012
DOI: 10.1002/dvdy.23833
|View full text |Cite
|
Sign up to set email alerts
|

Morphogenesis of outflow tract rotation during cardiac development: The pulmonary push concept

Abstract: Background: Understanding of cardiac outflow tract (OFT) remodeling is essential to explain repositioning of the aorta and pulmonary orifice. In wild type embryos (E9.5-14.5), second heart field contribution (SHF) to the OFT was studied using expression patterns of Islet 1, Nkx2.5, MLC-2a, WT-1, and 3D-reconstructions. Abnormal remodeling was studied in VEGF120/120 embryos. Results: In wild type, Islet 1 and Nkx2.5 positive myocardial precursors formed an asymmetric elongated column almost exclusively at the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 49 publications
(61 reference statements)
1
43
0
Order By: Relevance
“…Fernandez et al [23] suggested that particularly type 1 BAV results from abnormal neural crest cell behavior. Our data may indicate that also the sidedness of neural crest contributions may be of relevance, as was shown previously for second heart field contributions to the outflow tract [34]. Further study in larger, unselected (non-TS) cohorts is required to support this hypothesis.…”
Section: Discussionsupporting
confidence: 75%
“…Fernandez et al [23] suggested that particularly type 1 BAV results from abnormal neural crest cell behavior. Our data may indicate that also the sidedness of neural crest contributions may be of relevance, as was shown previously for second heart field contributions to the outflow tract [34]. Further study in larger, unselected (non-TS) cohorts is required to support this hypothesis.…”
Section: Discussionsupporting
confidence: 75%
“…Because it is much easier to identify and illustrate cardiac defects in 3-D, images of histological sections are often segmented and cardiac structures reconstructed in silico (e.g., Newbern et al, 2008; Scherptong et al, 2012; Briggs et al, 2013) (example in movie Figure 1S in Supplementary Material). The challenge of 3-D reconstruction is that sections are likely to be at slightly different angles and rotations or deformed during the collection of sections on slides so that adjustments of the images must be made by eye or by using computer programs to semi-automatically register the images.…”
Section: The Biophotonic Toolsmentioning
confidence: 99%
“…This could be because specific SHF populations failed to make their normal contribution to the OFT. RV/OFT walls are formed from cells originating in different areas of SHF(Bertrand et al, 2011; Dominguez et al, 2012; Takahashi et al, 2012) and their regional contribution to the tube may act to displace others in relation to the axes of the rest of the heart, i.e., relative ‘rotation’(Bajolle et al, 2006; Scherptong et al, 2012), including forming the distinctive subpulmonary myocardial population essential for normal truncal origin position and proximal trunk wall cells. We observed consistent regions of abnormally thin and thick OFT walls, areas of thickened trunk wall, and an insufficiency of sub-pulmonary myocardium suggesting AcvR1 and BmpR1a-mediated BMP signaling is required for normal formation, location and differentiation of specific SHF cell populations.…”
Section: Discussionmentioning
confidence: 99%